Distribution of the organic contamination in Bahia de Nipe, Cuba - T Romero-López; G Suárez-Alvarez (Ciencias Marinas, 1993)
A study was carried out on the water quality in Bahía de Nipe, with an approximate volume of 1,700 million cubic meters and average depth of 7 m, located NE of the eastern region of Cuba (75º40′ W, 20º50′ N). A network of 37 stations was established and seven cruises were conducted during and at the end of the sugar cane harvest season. The usual parameters of water quality, such as dissolved oxygen, biochemical oxygen demand, nitrite, nitrate, ammonium and total suspended solids, were analysed and it was found that the area with greater organic contamination was the one adjoining the effluents of the Guatemala agro-industrial complex (Central, Torula and Matadero). This was also corroborated by cluster analysis. The concentrations recorded confirmed that the condition of the bay deteriorates during the sugar cane harvest season, because of the high hydraulic and contaminant load contributed by the effluent sources. It is concluded that the Guatemala agro-industrial complex is mainly responsible for the environmental deterioration of the area and that the organic contamination must be controlled, in support of the fisheries and environmental health of the bay.